Pengaruh Total Asset Turnover, Current Ratio, Ukuran Perusahaan Terhadap Nilai Perusahaan Melalui Profitabilitas Sebagai Intervening - Fitriani, Salma Fadhilah; Komara, Esi Fitriani (Akuisisi : Jurnal Akuntansi, 2024)
What is to be achieved with research to investigate and prove the effect of total asset turnover, current ratio and company size on firm value with return on assets as an intervening variable in the apparel & luxury goods sub-sector listed on the IDX totaling 18 companies in accordance with the sample criteria. The methodology used is quantitative and uses secondary data. Data analysis using path analysis.  The results of this study are that return on assets is positively influenced by total asset turnover, while return on assets can be influenced by current ratio and company size. Firm value is positively influenced by total asset turnover and return on assets, while firm value cannot be influenced by current ratio and firm size. Return on assets can mediate total asset turnover on firm value, but is unable to mediate the current ratio and firm size on firm value